TEKNIK KOMUNIKASI DA’I DALAM MENCEGAH PERGAULAN BEBAS REMAJA MUSLIM DI KELURAHAN SIJAMBI KOTA TANJUNG BALAI - M. Darma Marpaung; Efi Brata Madya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
This research was conducted to find out the da'i's communication techniques in preventing the promiscuity of Muslim youth in the Sijambi sub-district, Tanjungbalai city. This research uses descriptive qualitative research with observation techniques, interviews, and document review studies. The location of this research was carried out in the Sijambi sub-district, Datuk Bandar sub-district, Tanjungbalai city, North Sumatra province with four informants. In this study, it can be concluded that the causes of promiscuity in the Sijambi sub-district are lack of parental attention, having a family that is not harmonious, getting influence from peers, and the influence of social media. Several communication techniques used by preachers to prevent promiscuity are persuasive communication techniques and interpersonal communication such as sharing, venting, or preaching. The obstacle of preachers in spreading preaching about promiscuity in the Sijambi sub-district of Tanjungbalai city is that there are parents who are overprotective, teenagers are less enthusiastic, preachers deliver boring material, and there is often competition between preachers. The solution to this problem is to provide direction to parents, preach with slang or current words, and strengthen relationships between preachers.